1996
DOI: 10.1073/pnas.93.17.8820
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci and metabolic pathways: genetic control of the concentration of maysin, a corn earworm resistance factor, in maize silks.

Abstract: Interpretation of quantitative trait locus (QTL) studies of agronomic traits is limited by lack of knowledge of biochemical pathways leading to trait expression. To more fully elucidate the biological significance of detected QTL, we chose a trait that is the product of a well-characterized pathway, namely the concentration of maysin, a C-glycosyl flavone, in silks of maize, Zea mays L. Maysin is a host-plant resistance factor against the corn earworm, Helicoverpa zea (Boddie). We determined silk maysin concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
143
1
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(156 citation statements)
references
References 30 publications
8
143
1
4
Order By: Relevance
“…Although our data do not rule out the possibility of an additional factor involved in maysin biosynthesis located between p1 and p2, the simplest interpretation of our results is that the p2 gene is sufficient to confer weak maysin levels, while p1 and p2 together produce higher maysin levels and stronger silk browning. These results further support the hypothesis that the p1 and p2 genes are essential coregulators of maysin biosynthesis (Byrne et al 1996;P. Zhang et al 2003;Szalma et al 2005).…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…Although our data do not rule out the possibility of an additional factor involved in maysin biosynthesis located between p1 and p2, the simplest interpretation of our results is that the p2 gene is sufficient to confer weak maysin levels, while p1 and p2 together produce higher maysin levels and stronger silk browning. These results further support the hypothesis that the p1 and p2 genes are essential coregulators of maysin biosynthesis (Byrne et al 1996;P. Zhang et al 2003;Szalma et al 2005).…”
Section: Resultssupporting
confidence: 78%
“…The region in the vicinity of p1 has been identified as a major QTL for the control of levels of silk maysin, a C-glycosyl flavone that deters feeding by corn earworm (Byrne et al 1996;Lee et al 1998;McMullen et al 1998). Maysin accumulation is correlated with a phenotype termed silk browning, in which the cut ends of silks turn brown due to the oxidation of flavones (Byrne et al 1996;Lee et al 1998;McMullen et al 1998;Guo et al 2001;Rector et al 2003).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In maize, the only case to date where the complete set of genes from a pathway has been examined, the maysin content of corn silks was associated with alleles of both regulatory and structural loci (1)(2)(3)(4). Other results from both maize (5,6) and Arabidopsis thaliana (7) have shown that variability in quantitative measurements of overall enzymatic activity can be attributed to structural loci or closely linked elements.…”
mentioning
confidence: 89%